Exploring strategies for enhancing access to oral healthcare for adults in Australia: a scoping review - Jayasekara Liyana Patabendige, Chaminda; Jenkins, Nicolie; Malatzky, Christina; Rohde, Alexia; McGowan, Kelly; Naicker, Sundresan (Frontiers in Oral Health, 2025)
Publicly funded adult oral healthcare services are mostly excluded in Australia's universal health coverage, despite oral disease being among the most common and costly health problems. Australia's vast land area and significant cultural diversity represent further challenges to ensuring equitable access to oral healthcare. A scoping review with the objective of synthesising and describing interventions aimed at improving access to oral healthcare for Australian adults was conducted, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews process. Four online databases (Web of Science, EMBASE, PubMed and CINAHL) and grey literature (via Google Advanced) were searched and multistage systematic screening and data charting processes were undertaken following the JBI manual. Thirty eligible records were identified. Eligible studies included the following target populations: First Nations, rural and remote populations (n = 10), homeless people and people with mental illness (n = 8), elderly communities (n = 6), public service consumers (n = 5), pregnant women (n = 4) and people with chronic diseases (n = 3). Studies included the following health workforce: dental care providers (n = 20), students and trainees (n = 5) and non-dental health professionals (n = 5). Interventions described at workforce level included: multidisciplinary care (n = 12), financial approaches (n = 7), expanded scope of practice (n = 7), academic collaborations (n = 5), public care coordination (n = 4) and technological applications (n = 3). The majority (n = 21) indicated successful interventions. Most studies (n = 11) included fewer than 40 participants or were pilot interventions (n = 10). The interventions described may be scaled to other similar settings. To achieve universal health coverage, innovative models emphasising flexible workforce skills, task-sharing and multidisciplinary care are needed.